2000
DOI: 10.1001/archneur.57.7.983
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa Withdrawal After Bilateral Subthalamic Nucleus Stimulation in Advanced Parkinson Disease

Abstract: Bilateral STN stimulation safely improves all parkinsonian symptoms, decreases or eliminates the need for levodopa, and ameliorates motor fluctuations and dyskinesias. Complete withdrawal of levodopa is feasible with this technique and the overall motor effect of STN stimulation is quantitatively comparable to that obtained with levodopa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
118
1
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 187 publications
(142 citation statements)
references
References 36 publications
17
118
1
6
Order By: Relevance
“…Several studies have demonstrated that dopaminergic medications influence hallucinations in PD and that they are associated with increased age and longer disease duration [23] [24] [25]. In this present study, hallucinations were associated with increased age and longer disease duration, which is consistent with the current literature.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have demonstrated that dopaminergic medications influence hallucinations in PD and that they are associated with increased age and longer disease duration [23] [24] [25]. In this present study, hallucinations were associated with increased age and longer disease duration, which is consistent with the current literature.…”
Section: Discussionsupporting
confidence: 92%
“…(off-medication, worstoff motor condition: Off-Med) 6-12 Unified Parkinson Disease Rating Scale (UPDRS) [3][4][5][6][7][8][9] (UPDRS part II) 44-72% (UPDRS part III) 38-66%…”
Section: パーキンソン病に対する視床下核 Dbs (Stn-dbs) Stn-dbs の短期成績mentioning
confidence: 99%
“…However, the assessment of the effectiveness of DBS for the treatment of symptoms is generally limited by the number of individuals analysed; significant losses to follow-up in some studies; and follow-up of the participants to a maximum of only 48 months. The reduction in antiparkinsonian medication after DBS may also significantly reduce some of the side effects of high-dose levodopa treatment over a long time (Charles et al, 2004;Mínguez-Castellanos et al, 2005;Molinuevo et al, 2000). Most of the studies on cost-effectiveness in STN-DBS have been designed in the absence of a control group of similar characteristics receiving conventional oral medication supposed to be the BMT possible.…”
Section: Cost-effectiveness Of Bilateral Subthalamic Stimulation In Amentioning
confidence: 99%